Prospects for using the phytoremediation method for deactivation of territories contaminated with radionuclides - Tsybulka, Mikalai; Rodzkin, Aleh (Journal of the Belarusian State University. Ecology, 2023)
Soil contamination with radionuclides, the main cause of which is the accident at the Chernobyl nuclear power plant, is one of the most dangerous negative environment impact factors. Phytoremediation including cultivation of «energy» crops is an effective method for decontamination of territories contaminated with radionuclides. The advantage of this approach is the possibility of using biomass as a renewable source of green energy in combination with the gradual reclamation of polluted soils. A promising crop for the purposes of phytoremediation is willow, the fast-growing species of which provide a high yield of biomass from a production plantation. A problematic issue is the safe use of willow biomass. The assessment of the conditions for the transition of radioactive cesium into willow biomass was carried out on the territories of Belarus contaminated after the Chernobyl accident. Experiments have shown that the predicted content of 137Cs in the wood of a fast-growing willow is significantly lower than the level allowed for wood fuel according to the standards established for the Republic of Belarus (740 Bq/kg). Even at the level of soil pollution at which they are removed from agricultural use (40 Ci/km2), the content of 137Cs in wood will be from 35 to 120 Bq/kg (depending on the dose of potash fertilizers).